Meta-analysis of brucellosis vaccinology in natural hosts - Carvalho,Tatiane F. (2020)
ABSTRACT: Brucellosis is a relevant zoonotic disease for which the most important tool for control is vaccination of susceptible animals. Assessment of vaccine efficacy in natural hosts is based on prevention of abortion and Brucella infection in organs of immunized animals. A meta-analysis of experimental vaccination of Brucella spp. natural hosts was performed, including 45 PubMed and/or Scopus-indexed publications, representing 116 individual experiments. Difference of risk was calculated as an indicator of protection, and a temporal analysis (1980-2016) demonstrated that experimental vaccines tested on natural hosts provided levels of protection that were stable over the past decades. The meta-regression model developed in this study included different vaccine categories (attenuated, inactivated, mutant, subunit, and vectored) considering the difference of risk as the dependent variable. The subcutaneous route of vaccination provided better protection when compared to the intramuscular and oral routes of vaccination. Surprisingly, inactivated vaccines provided better protection than live naturally attenuated vaccine strains (spontaneous mutations) that were considered the reference, whereas subunit vaccines provided lower levels of protection. This is the first meta-analysis of Brucella vaccinology in the natural hosts. These results are useful for the development of new vaccination protocols for controlling animal brucellosis.